2001
DOI: 10.1159/000053802
|View full text |Cite
|
Sign up to set email alerts
|

Are Mast Cells MASTers in HIV-1 Infection?

Abstract: HIV-1 gp120 interacts with IgE VH3+ on the surface of human basophils and mast cells (FcΕRI+ cells), acting as a viral immunoglobulin superantigen. gp120 from different clades induces mediator release from FcΕRI+ cells. gp120 also induces IL-4 and IL-13 synthesis in human basophils. The chemokine receptors CCR3 and CXCR4, which are coreceptors of HIV-1 infection, are expressed by human FcΕRI+ cells. HIV-1 Tat protein is a potent chemoattractant for basophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 63 publications
(139 reference statements)
0
17
0
Order By: Relevance
“…85,86 For example, dengue virus and HIV have been shown to infect MCs and to induce MC cytokine and chemokine production in vitro. 85,87,88 In addition, encephalomyocarditis virus infection reportedly results in MC chymase and tryptase production in vivo 89 and viral infections have been shown to cause accumulation of MCs in the nasal mucosa during the first days of a symptomatic naturally acquired respiratory infection. 90 However, the relevance and underlying mechanisms of MC infection and activation in settings of viral infections remain to be characterized in detail.…”
Section: Discussionmentioning
confidence: 99%
“…85,86 For example, dengue virus and HIV have been shown to infect MCs and to induce MC cytokine and chemokine production in vitro. 85,87,88 In addition, encephalomyocarditis virus infection reportedly results in MC chymase and tryptase production in vivo 89 and viral infections have been shown to cause accumulation of MCs in the nasal mucosa during the first days of a symptomatic naturally acquired respiratory infection. 90 However, the relevance and underlying mechanisms of MC infection and activation in settings of viral infections remain to be characterized in detail.…”
Section: Discussionmentioning
confidence: 99%
“…[25]. Other viral products and mediators produced during viral infection, such as protein Fv, can enhance human mast cell and basophil activation through interactions with Fc receptors [26,27].…”
Section: Viral Infectionmentioning
confidence: 99%
“…More recently, similar properties have been shown to be shared by a number of viral proteins or host proteins upregulated as part of the antiviral response. 1,2 Direct evidence of a role for mast cells in host defense against bacterial pathogens did not become available until the mid-1990s after studies that indicated that mast cells could produce cytokines in response to LPS without degranulation. 3 In both a model of cecal ligation and puncture 4 and a model of Klebsiella pneumoniaeinduced peritonitis, 5 mice with normal numbers of mast cells survived bacterial challenge, whereas mast celledeficient W/Wv mice succumbed to infection.…”
Section: Evidence For Mast Cells Having a Role In Innate Immunitymentioning
confidence: 99%
“…A variety of Toll activators have been defined, which include products from all classes of mammalian pathogens, as well as endogenous proteins, some of which are known to activate mast cells (Table I). 1,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] For example, TLR4 has been shown to mediate responses to most types of LPS, as well to a number of other pathogen products, and to heat shock protein 60, which might be released on cell stress. In contrast, TLR2 mediates responses to peptidoglycan from many gram-positive bacteria and the yeast cell-wall component zymosan, whereas TLR9 mediates responses to CpG motifs found within bacterial DNA.…”
Section: Mechanisms Of Mast Cell Activation In Innate Immunity Tlrsmentioning
confidence: 99%